2014
DOI: 10.1177/204124791400500401
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biocomposites from Cocoa Pod Husk and Polypropylene: Effect of Filler Content and 3-Aminopropyltriethoxylsilane

Abstract: Cocoa pod husk (CPH) is a waste material from cocoa industry. This work describes the development of biocomposites from polypropylene and cocoa pod husk. 3-aminopropyltriethoxysilane (3-APE) is used as coupling agent in filler treatment of CPH. The treated CPH with 3-APE had raised the stabilization torque of PP/CPH biocomposites. The results of tensile test and scanning electron microscope (SEM) indicated that 3-APE given coupling effect on PP/ CPH biocomposites. The presence of covalent bonds between CPH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Thus, the flexibility of PP matrix was reduced by the stronger filler-matrix adhesion. Other researchers reported a similar influence of silane coupling agent 20 and SDS 22 on the elongation at break of PP/chitosan composites.…”
Section: Tensile Propertiessupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, the flexibility of PP matrix was reduced by the stronger filler-matrix adhesion. Other researchers reported a similar influence of silane coupling agent 20 and SDS 22 on the elongation at break of PP/chitosan composites.…”
Section: Tensile Propertiessupporting
confidence: 53%
“…12,13 Thus, many researchers reported that the silane coupling agent does remarkably to improve the water resistivity and mechanical and thermal properties of composites. [12][13][14][15][16][17][18][19][20][21] Moreover, some literatures reported that the use of fatty acid for filler treatment will also give a coupling effect to the composites. Fatty acid is made from sustainable resources, and it is inexpensive compared to commercial silane coupling agent.…”
Section: Introductionmentioning
confidence: 99%
“…According to thermogravimetry results [20] the obtained weight losses during carbonization were 10.27%, 13.56 % and 17.64% at temperatures of 250, 300 and 400°C, respectively. The strong decrease in weight at 400°C corresponds to the decomposition of lignocellulose whereas at 250°C is attributed to the decomposition of hemicellulose [22]. Thermal degradation has taken place through heat supplied during the carbonization process [5].…”
Section: Structure Of Cacao Pod After Carbonizationmentioning
confidence: 99%
“…Figure 6 illustrates the morphology and particle of cocoa before being delegated (depectination) and cocoa that has been delegated. Morphology shows that delignified cocoa has a smaller cavity compared to depectative Figure 2b, having a thicker and rougher surface to protect the lignocellulosic content contained in fiber [28]. The significant difference in the two samples lies in the particle size.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 97%